PERAN AUDIT INTERNAL, MANAJEMEN PERUSAHAAN DAN PENCEGAHAN KECURANGAN TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA PT UNIVERSAL- CAR RENTAL) - Krisnawati Tarigan; Viorentine (Jurnal Akuntansi, 2021)
The purpose of this research is to determine the role of internal audit on employee performance, to analyze and to know the role of company management on employee performance and to know in priority how to prevent fraud on employee performance. This research was conducted and limited to 1 year, which was taken by interviewing and distributing questionnaires to parties closely related to the company such as employees at the Universal Car rental company. The data analysis method used is a qualitative method. The data source used in this research is secondary data. Data collection techniques through interviews, documentation and literature study. Based on the conclusions drawn in this study, the results of testing for internal auditors, company management and fraud prevention in employee performance can be proven by analysis of interviews from sources who are working at Universal Car company. From the results of the interview, it can be concluded that internal audit, company management and fraud prevention have a significant and acceptable relationship.   Keywords: internal audit, company management, prevent fraud, employee performance.